Strike actions by nurses/midwives in a nursing service - Elsie Mabange; Marie Muller (AOSIS, 2000)
Strike actions by nurses/midwives in a health service could have substantial implications for the patients, the health service management, the staff and the nursing profession at large. The nursing service manager has a legal obligation to prevent strike action by nurses/midwives by means of quality human resource management. The purpose of this research is to develop a strategy to prevent strike action by nurses/midwives in a nursing service. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.